PENGEMBANGAN USAHA KECIL MENENGAH BERBASIS 4.0:FESYEN XUSHA DI KOTA BANDUNG ERA PANDEMI COVID – 19 - Taufik, Taufik; Afriantari, Rini (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2023)
Small and medium enterprises in Indonesia are one of the cornerstones of a new developing economy, including Indonesia. Many creative young people develop various businesses by looking at the times and market needs. Bandung, or Paris Van Java, is a tourist destination famous for its